RANCANG BANGUN SISTEM PROTEKSI OVERHEATING MESIN DAN PEMANTAU TEGANGAN AKI PADA MOBIL - Ahmad Yuvi Utomo (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
Abstract – Overheating is one of the causes of damage or decreased performance on the vehicle. This can occur due to a lack of water in the radiator or a radiator leak. Generally, overheating occurs in vehicles manufactured before 2000 because they do not have protection or warning in case of excessive temperature. Vehicles with production years before 2000 usually only have a temperature indicator in the form of a pointer with a scale. In addition to overheating, the voltage on the battery cannot be monitored due to the absence of a battery voltage reader so that the battery experiences under-voltage or overvoltage caused by damage to the charging system in the battery. Based on these problems, a tool is made to prevent overheating and prevent damage to the battery. In this tool, the DS18b20 sensor is used to determine the temperature that occurs in the vehicle engine, while the battery voltage information is obtained using a voltage divider circuit. The results of the temperature and voltage sensors are processed using the Arduino Nano Microcontroller to obtain information about the engine temperature and battery voltage. The processing results are displayed using an OLED LCD and the output is connected to two relays, one relay for automatic fans and one relay for vehicle ignition. The results showed that this tool can turn on and turn off the fan automatically, and can cut off the ignition of the vehicle based on the temperature of the radiator water. This tool provides a warning if the battery voltage is above or below the normal voltage. With this tool, overheating of the engine and damage to the battery can be prevented. Keywords Overheating, protection, temperature